ChemInform Abstract: Diborane‐Mediated Deoxygenation of o‐Nitrostyrenes to Form Indoles. Issue 52 (6th December 2016) - Yang, Kai; Zhou, Fei; Kuang, Zhijie; Gao, Guoliang; Driver, Tom G.; Song, Qiuling
Abstract: A mild, reductive cyclization of ortho‐nitrostyrenes affords indoles via in situ generated nitroso arenes.